The contribution of mobile banking on business growth, perceptions of sme customers of NMB Bank: A case of Kenyatta road branch, Mwanza Tanzania - Lugangira, David (Mzumbe University, 2024)
A dissertation submitted in partial fulfillment of the requirements for award of the Masters of Business Administration (MBA) of Mzumbe University